Do charter schools crowd out private school enrollment? Evidence from Michigan - Rajashri Chakrabarti; Joydeep Roy (Federal Reserve Bank of New York, 2010)
Charter schools have been one of the most important dimensions of recent school reform measures in the United States. Currently, there are more than 4,500 charter schools spread across forty U.S. states and the District of Columbia. Though there have been numerous studies on the effects of charter schools, these have mostly been confined to analyzing the effects on student achievement, student demographic composition, parental satisfaction, and the competitive effects on regular public schools. This study departs from the existing literature by investigating the effect of charter schools on enrollment in private schools. To investigate this issue empirically, we focus on the state of Michigan, where there was a significant spread of charter schools in the 1990s. Using data on private school enrollment from decennial censuses and biennial National Center for Education Statistics private school surveys, and using a fixed-effects as well as instrumental-variables strategy that exploits exogenous variation from Michigan charter law, we investigate the effect of charter school penetration on private school enrollment. We find some evidence of a decline in enrollment in private schools - but the effect is only modest in size. This finding is reasonably robust, and survives several robustness checks.
Keywords: H4; I21; I28; 330; Charters; private schools; instrumental variables